Quick Tecniques in Indentifying Open Area by the Use of Multi Spatial and Multidate Imageries - Ahyar Gunawan; I Nengah Surati Jaya; Muhammad Buce Saleh (Institut Pertanian Bogor (IPB University), 2010)
This study describes the use of multitemporal principal component analysis (MPCA) and vegetation index differencing (VIDN) techniques in identifying open area on post-coal mining sites using multi spatial and multidate of Landsat TM and SPOT 4 XS imageries. The study revealed that the synthetic images derived from stable brightness, stable greenness,s and delta brightness of MPCA summarize information on post-coal-mining opened areas provided overall accuracy of 76.47% for the new ex mining area and 32.69% for old ex mining area. The VIDN method provided relatively lower accuracy than those from MPCA i.e. 58.87% for new ex mining and 13.25% for old ex-mining areas. The study also concluded that identifying open area on post-coal-mining sites using imageries was more efficient than using only ground survey, providing cost efficiency of 29%. Thisindicates that the cost required using satellite image is only 29% of the cost required for ground survey. The study concluded that MPCA is better than VIDN for identifying open area on post-coal-mining sites.